Dev.Learn - Relato de experiência de um curso de extensão para ensinar a desenvolver sites - Tomazini, Miguel Rodrigues; Jönck, Letícia Raddatz; Paffaro, Pedro Augusto Ferraro; Santos, Gabriel Barbosa dos; Bruschi, Sarita Mazzini (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This paper reports on a community outreach course focused on web development, conducted by the USPCodelab Sanca group. With a mission to foster technological innovation at USP, this initiative aimed to empower high school students from local schools by promoting their digital inclusion. The course featured weekly theoretical and practical classes with one-on-one mentorship, using essential technologies such as HTML, CSS, and introductory JavaScript. This experience demonstrated the potential of university outreach to create a significant social impact, aligning directly with the UN Sustainable Development Goal 4 (Quality Education) and Goal 8 (Promote sustained economic growth). The course not only increased participants’ interest in technology, but also effectively transitioned them from passive technology consumers to active creators, achieving meaningful digital inclusion.